DANA ALOKASI KHUSUS DAN PENDAPATAN ASLI DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA (Studi Empiris pada Pemerintah Provinsi se-Indonesia Tahun 2012-2014) - Hastu Sarkoro; Zulfikar Zulfikar (Riset Akuntansi dan Keuangan Indonesia, 2016)
The purpose of this research is to examine the significant impact of Local Government Expenditure, General Allocation Fund, Special Allocation Fund and Original Local Government Revenue in Human Development Index at Province Governance in Indonesia. The method of this research is purposive sampling with 33 province as a sample for every year from 34 province at Indonesia  for 2012-2014 period. This research utilizies secondary data. The data are taken from the website BPS Statistic Indonesia (www.bps.go.id). The data which is analyzed in this research are collected through the realitation revenue and expenditure of provincial government. The data which have already collected are processed with classic assumption test before hypothesis test. Hypothesis test in this research use multiple regression with t test, F test and coefficient determination test. The result of this research show that partially Local Government Expenditure and Original Local Government Revenue have a positive significant impact to the Human Development Index. Whereas, General Allocation Fund and Special Allocation Fund have a negative significant impact to the Human Development Index. Local Government Expenditure, General Allocation Fund, Special Allocation Fund and Original Local Government Revenue have a positive significant impact to the Human Development Index simultaneously.